Electrochemical analysis of the corrosion inhibition properties of L-leucine and trypsin complex admixture on high carbon steel in 1 M H2SO4 solution (2018)
Corrosion inhibition of biodegradable chemical compounds (L-leucine and trypsin complex) on high carbon steel in 1 M H2SO4 acid media was evaluated with potentiodynamic polarization technique, weight loss analysis, open circuit potential measurement, optical microscopy, and ATR-FTIR spectroscopy. Data obtained showed the mixture has a maximum inhibition efficiency of 82.4% and 90.08% from the electrochemical tests with mixed type inhibition properties. The addition of the mixture shifts significantly the corrosion potential of the steel to passivation values from open circuit potential measurement. Results from thermodynamic calculations indicated chemisorption adsorption mechanism according to Langmuir, Freundlich, and Frumkin isotherms coupled with correlation coefficients of 0.9994, 0.9651 and 0.8834. Statistical analysis showed exposure time to be the most significant variable responsible for corrosion inhibition. Identified functional groups of the compound from ATF-FTIR spectroscopy were adsorbed completely on the carbon steel surface from observation of the decreased peak intensity. Optical microscopy images of the inhibited and uninhibited steel surfaces contrast each other with due to the presence of macro-pits and porous oxide on the uninhibited steel.